Infografika kao oblik komunikacije na području zaštite zdravlja i sigurnosti na radu - Machala Poplašen, Lovela (Array, 2020)
Infographics are a communication tool used in the digital environment that can present information, data or knowledge in an easy and understandable way to a wider audience. This article presents infographics as a form of communication and describes and outlines its possibilities in the field of public health and health care, with special emphasis on health and safety at work.Visualization of key statistical data, standardized elements, systems and practices in the style of infographics enables health and safety specialists to easily educate their employees about the consequences of poor health, the risks involved in work processes and the non-implementation of work safety processes and safety measures. The paper analyzes available infographics of leading institutions in the field of health and work safety in Croatia and in the world. Infographics are a recognizable form of communication worldwide. However, there is only a small number of infographics in the field of health and work safety in Croatia. It is important to raise awareness of the importance of infographics among Croatian experts working in the field of health and work safety because of the possibilities that infographics offer as a form of communication. Infographics should not be neglected because they can be used to present important information and directions in an easily understandable and universal way to various audiences.